Equity valuation: Nestlé S.A. - Martins, Tiago Fernandes de Macedo (2018)
Equity investment decisions are partially based on expected share price increases. Other factors may influence an investment decision, such as risk, expected dividends and portfolio diversification. In this perspective, one must establish an opinion regarding the value (or expected value) of the issuer. According to Damodaran (2012), three approaches can be used to value a company: option pricing models, discounted cash flow models and relative valuation. Within each approach, different models can be used. Most models include parameters that carry some subjectivity, such as cash flow forecasting, growth rates, market conditions and several others. This means that, even though valuation models are quantitative, valuation is subjective. "If a business is complex and subject to constant change, we’re not smart enough to predict future cash flows" - Warren Buffett. In this study we analyze and value Nestlé, the number one consumer goods company in the world in terms of sales. We then compare our valuation with the market's and conclude whether the company is under or overvalued (under the scope of our assumptions). To do so we use the following valuation methods: Free Cash Flow to the Firm (FCFF) and Relative Valuation through peer group multiples. We then compare our research to an investment bank's to understand whether the valuation (based on the assumptions we make) is realistic. Our results indicate that Nestlé shares were priced below their true value as at 31-12-2016. Therefore, we would have recommended buying the stock at that time.